2013
DOI: 10.4049/jimmunol.1202456
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Receptor Regulates microRNA-135b Expression in a Negative Feedback Mechanism during Cigarette Smoke–Induced Inflammation

Abstract: Although microRNA-135b (miR-135b) is known to be associated with cancer, with recent work showing that it is massively induced in the pulmonary tissues of mice challenged with nanoparticles suggests a critical role for this microRNA in mediating inflammatory response. In this study, we investigated the expression and function of miR-135b in mice exposed to cigarette smoke or nontypeable Haemophilus influenzae (NTHi). Exposure to both cigarette smoke and NTHi elicited robust lung inflammation, but increased miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 26 publications
0
42
0
1
Order By: Relevance
“…An additional study in smokeexposed mice found that miR-135b abundance increased in the respiratory tract (Halappanavar et al, 2013). miR135b decreased the expression of interleukin 1 receptor (IL-1R1) through its 3′ UTR and was also a target of signaling through the IL-1 pathway, suggesting this miRNA as a critical regulator of IL-1-mediated neutrophilic inflammation (Halappanavar et al, 2013). Furthermore, miR-218-5p was found to be significantly downregulated in lung tissue of smoke-exposed mice and humans (Conickx et al, 2017).…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study in smokeexposed mice found that miR-135b abundance increased in the respiratory tract (Halappanavar et al, 2013). miR135b decreased the expression of interleukin 1 receptor (IL-1R1) through its 3′ UTR and was also a target of signaling through the IL-1 pathway, suggesting this miRNA as a critical regulator of IL-1-mediated neutrophilic inflammation (Halappanavar et al, 2013). Furthermore, miR-218-5p was found to be significantly downregulated in lung tissue of smoke-exposed mice and humans (Conickx et al, 2017).…”
Section: Copdmentioning
confidence: 99%
“…Higher levels of smoke exposure corresponded to greater alterations in more miRNAs, most of which returned to baseline following smoking cessation, though some did not (Izzotti et al, 2011). An additional study in smokeexposed mice found that miR-135b abundance increased in the respiratory tract (Halappanavar et al, 2013). miR135b decreased the expression of interleukin 1 receptor (IL-1R1) through its 3′ UTR and was also a target of signaling through the IL-1 pathway, suggesting this miRNA as a critical regulator of IL-1-mediated neutrophilic inflammation (Halappanavar et al, 2013).…”
Section: Copdmentioning
confidence: 99%
“…It is noteworthy that these miRNAs have human homologues and thus may be involved in the response to cigarette smoke exposure in humans as well. In a mouse model of 4 days' cigarette smoke exposure, miR-135b was shown by qRT-PCR to be increased in lung tissue samples [20]. The authors suggest that the upregulation of miR-135b may act as a counter-regulatory mechanism for cigarette smoke-induced inflammation, by regulating the IL-1 receptor (IL-1R1) expression.…”
Section: Introductionmentioning
confidence: 98%
“…This immune-pulmonary cell microenvironment is the foundation of the pulmonary innate and/or adaptive immune systems [25] . Recently, a research group has reported a series of results showing the dominant up-regulation of miR-135b in lung tissues upon exposure to cigarette smoke and nano-particles in mice models [26][27][28] . The activated miR-135b is mediated through the IL-1a/IL-1R pathway, which consequently triggers either the acute or chronic pulmonary inflammation signaling cascade [26][27][28] .…”
Section: Rolementioning
confidence: 99%
“…In addition, using miR-135b inhibitors, several researchers have shown that silencing of miR-135b mitigates tumor burden, relieves lung metastatic nodules, and even rescues APC-knockout caused phenotypes [18,22] . Furthermore, miR-135b displays immuno-modulatory ability by cross-talking with pro-inflammatory cytokines and T cells in anaplastic large-cell lymphoma (ALCL) and in lung cancers [26,31] . Thus, miR-135 inhibition may further block the communication between tumor cells and its surrounding cancer niche.…”
Section: The Mir-135b As a Therapeutic Target For Cancer And Future Pmentioning
confidence: 99%